Some Notes about Arrangements of Points on Quadrics - A. V. Seliverstov (Моделирование и анализ информационных систем, 2015)
It is considered the minimization of a quadratic polynomial on the set of all points of a multidimensional space, coordinates of which are either zero or one. Some restrictions are imposed on the arrangement of the minimum points when there are many such points.combinatorial optimization, quadratic programming, empty quadric, polytope, facet